A thermally polarized 129Xe phantom for quality assurance in multi‐center hyperpolarized gas MRI studies. Issue 5 (19th June 2019) - Bier, Elianna A.; Nouls, John C.; Wang, Ziyi; He, Mu; Schrank, Geoff; Morales‐Medina, Naomi; Hashoian, Ralph; Svetlik, Harvey; Mugler, John P.; Driehuys, Bastiaan
Abstract : Purpose: Hyperpolarized 129 Xe MR is increasingly being adopted worldwide, but no standards exist for assessing or comparing performance at different 129 Xe imaging centers. Therefore, we sought to develop a thermally polarized xenon phantom assembly, approximating the size of a human torso, along with an associated imaging protocol to enable rapid quality‐assurance imaging. Methods: MR‐compatible pressure vessels, with an internal volume of 5.85 L, were constructed from pressure‐rated, engineering grade PE4710 high‐density polyethylene. They were filled with a mixture of 61% natural xenon and 39% oxygen to approximately 11.6 bar and placed in a loader shell filled with a 0.56% saline solution to mimic the human chest. Imaging employed a 2D spoiled gradient‐echo sequence using non‐slice‐selective excitation (TR/TE = 750/6.13 ms, flip angle = 74°, FOV = 40 × 440 mm, matrix = 64 × 32, bandwidth = 30 Hz/pixel, averages = 4), resulting in a 1.6 min acquisition. System characterization and imaging were performed at 8 different MRI centers. Results: At 3 Telsa, 129 Xe in the pressure vessels was characterized by T1 = 580.5 ± 8.3 ms, linewidth = 0.21 ppm, and chemical shift = +10.2 ppm. The phantom assembly was used to obtain transmit voltage calibrations and 2D and 3D images across multiple coil and scanner configurations at 8 sites. Across the 5 sites that employed a standard flexible chest coil, the SNR was 12.4 ± 1.8. Conclusion: The high‐density polyethylene pressure vessels filled with thermally polarized xenon and associated loader shell combine to form a phantom assembly that enables spectroscopic and imaging acquisitions that can be used for testing, quality assurance, and performance tracking—capabilities essential for standardizing hyperpolarized 129 Xe MRI within and across institutions.